TF-343 Alleviates Diesel Exhaust Particulate-Induced Lung Inflammation via Modulation of Nuclear Factor-κB Signaling - Dong Im Kim; Mi-Kyung Song; Seon-Hee Kim; Chan Young Park; Kyuhong Lee (Journal of Immunology Research)
Inhalation of diesel exhaust particulate (DEP) causes oxidative stress-induced lung inflammation. This study investigated the protective effects of TF-343, an antioxidant and anti-inflammatory agent, in mouse and cellular models of DEP-induced lung inflammation as well as the underlying molecular mechanisms. Mice were intratracheally instilled with DEP or vehicle (0.05% Tween 80 in saline). TF-343 was orally administered for 3 weeks. Cell counts and histological analysis of lung tissue showed that DEP exposure increased the infiltration of neutrophils and macrophages in the peribronchial/perivascular/interstitial regions, with macrophages harboring black pigments observed in alveoli. TF-343 pretreatment reduced lung inflammation caused by DEP exposure. In an in vitro study using alveolar macrophages (AMs), DEP exposure reduced cell viability and increased the levels of intracellular reactive oxygen species and inflammatory genes (IL-1β, inhibitor of nuclear factor- (NF-) κB (IκB), and Toll-like receptor 4), effects that were reduced by TF-343. A western blot analysis showed that the IκB degradation-induced increase in NF-κB nuclear localization caused by DEP was reversed by TF-343. In conclusion, TF-343 reduces DEP-induced lung inflammation by suppressing NF-κB signaling and may protect against adverse respiratory effects caused by DEP exposure.